BIOGRAFIA JĘZYKOWA JAKO PRZYCZYNEK DO REFLEKSJI NAD MOTYWACJĄ DO NAUKI JĘZYKA NIEMIECKIEGO - Mackiewicz, Maciej (Neofilolog, 2019)
A language biography is most often a reflection on one’s own linguistic development and therefore can be termed “language autobiography”. In its a broad sense, a language biography may include mother tongue acquisition, yet this article focuses solely on foreign language learning, with a special emphasis on the German language. The article provides insights into factors that motivate learners of German and into changes in these factors over a period of time, including the role of intercultural motivators. A theoretical and methodological introduction is followed by the results of a qualitative study conducted in five Polish institutions of tertiary education on a group of 73 students learning German. The excerpts of biographies quoted provide a picture of motivation as a dynamic process and moreover indicate that as present-day students get older, they are increasingly more thoughtful about their learning.